A facile synthesis of ternary hybrid nanocomposite of WS2/ZnO/PPy: An efficient photocatalyst for the degradation of chromium hexavalent. (February 2023) - Tyagi, Nahid; Ashraf, Waseem; Mittal, Honey; Fatima, Tarab; Khanuja, Manika; Singh, Manoj Kumar
Abstract: In this study novel and promising ternary hybrid nanocomposite of tungsten disulphide (WS2 ), zinc oxide (ZnO) and polypyrrole (PPy) has been synthesized for the efficacious photocatalytic reduction of hexavalent chromium (Cr(VI)). This ternary hybrid nanocomposite was prepared using the hydrothermal and in situ oxidative polymerization method. The crystal structures, physicochemical and optical features of the prepared nanocomposite were examined using various characterization techniques such as XRD, FTIR, and UV–Vis spectroscopy. The synthesized nanocomposite contains the morphologies of pristine samples such as nanosheets, nanorods and nanoparticles of WS2, ZnO and PPy, respectively as demonstrated from FESEM images. The adsorption and photocatalytic degradation studies were performed as a function of concentrations of Cr (VI). The synthesized nanocomposite shows enhanced degradation efficiency (81.82%–94.66%) from pristine samples (1.81–4.85% for WS2, 29.09–36.36% for ZnO and 45.55–48.94% for PPy) towards 10 mg/L concentration of Cr(VI) under dark and light conditions, respectively. This enhanced degradation efficiency was attributed to the large surface area, lower recombination rate for photogenerated species, superior absorption for light and generation of free radicals under dark and light conditions as explained by TCSPC decay, tauc's plot (2.28 eV) and EPR measurements, respectively. EPR and scavenger study both supports for the formation of free radicals ( O 2− ) and ( . OH) in light and dark both conditions. The value of g-factor comes out to be 2.01 from EPR study. The kinetic study illustrates that the photocatalytic degradation of Cr(VI) by the prepared ternary nanocomposite followed pseudo-second-order rate kinetics model and Langmuir adsorption isotherm. These models proposed that the removal of Cr(VI) was take place through both physisorption and chemisorption processes. The degradation mechanism was analyzed with the help of Mott-Schottky/scavenger studies, and revealed that the superoxide radicals ( O 2− ) were the primary active species. The reusability experiment demonstrates that the prepared nanocomposite can be reused up to 5 times with almost the same efficiency in all cycles and hence, can be considered as a promising candidate for wastewater treatment. Graphical abstract: Photocatalytic degradation of contaminants using ZWP ternary nanocomposite. Image 1 Highlights: Novel ternary nanocomposites of WS2 /PPy/ZnO are synthesized via hydrothermal and in situ oxidative polymerization method. Maximum degradation efficiency attained by ternary nanocomposite is 81.82% and 94.66% under dark & sunlight, respectively. EPR study confirms that (.O2 − ) and ( . OH) both radicals were formed under dark and light conditions. TCSPC analysis confirms a large average recombination time (2.75 ns) for the photogenerated electron/holes. Nanocomposites are proved effective & suitable materials for the degradation of contaminants through photocatalytic approach.